2022
DOI: 10.3390/w14162535
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Pattern Analysis of Land Use and Water Yield in Water Source Region of Middle Route of South-to-North Water Transfer Project Based on Google Earth Engine

Abstract: The water source area of the middle route of the South-to-North Water Diversion Project is an important water conservation and ecological protection area in China. Based on remote sensing data, this paper analyzed the evolution process of land use/cover change in water source region in the past 35 years. Then, based on the InVEST model, the spatial-temporal patterns of water yield in the water source region were calculated with land use cover, meteorology and soil data as inputs. The impacts of climate factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Fig. 4 Effective frontier calculation result graph After the calculation of the effective frontier, the global minimum variance combination, which is the leftmost vertex of the effective frontier curve and also the theoretically optimal weight allocation combination, can be solved according to Formulas (11) and (12). The results are shown in Table 3.…”
Section: Calculation Results Of the Modelmentioning
confidence: 99%
“…Fig. 4 Effective frontier calculation result graph After the calculation of the effective frontier, the global minimum variance combination, which is the leftmost vertex of the effective frontier curve and also the theoretically optimal weight allocation combination, can be solved according to Formulas (11) and (12). The results are shown in Table 3.…”
Section: Calculation Results Of the Modelmentioning
confidence: 99%
“…Cloud computing platforms, such as Google Earth Engine (GEE), allows the processing of large amounts of data for the understanding of climate and LULC changes on river basins, especially those located in arid and semi-arid regions (Souza et al 2020;Niu et al 2022). With the adequate analysis, remote sensing imagery techniques give important insights into how climate and land use changes affect, at different spatial and temporal resolutions, a basin and local communities (Alam et al 2020) and have been used to detect soil loss, deforestation rates, and water use at a regional level (Uddin et al 2018).…”
Section: )mentioning
confidence: 99%
“…Limitations to ground monitoring systems include slow, point-based measurements, which are often di cult to obtain and subjected to failures (Oularé et al 2023). In contrast, remote sensing technology provides comprehensible information that, when coupled with climatic and ground-based data, can become a powerful monitoring tool (Mekonnen et al 2017;Rodgers et al 2020;Niu et al 2022;Jiang et al 2023). However, processing satellite imagery demands high computing power, which has been a major limiting factor (Kang et al…”
Section: Introductionmentioning
confidence: 99%
“…This pattern is similar to the pattern of annual rainfall in the study area (Figure 2b), in which the high rainfall was found in the middle and the southwest of the CW. Previous studies reported that the spatial pattern of WY within the watershed is mainly influenced by precipitation [55,56]. Using a correlation analysis, ref.…”
Section: Spatial Patterns Of Ws and Wdmentioning
confidence: 99%